Intelligent and evolutionary systems : the 20th Asia Pacific Symposium, IES 2016, Canberra, Australia, November 2016 : proceedings /: the 20th Asia Pacific Symposium, IES 2016, Canberra, Australia, November 2016 : proceedings. ([2017]) - Unknown
No abstract available